Perancangan Antarmuka Berdasarkan Evaluasi Usabilitas Penggunaan Aplikasi KlikDokter Untuk Pralansia dan Lansia - Christianti Angelin Maarende; Danny Sebastian; Restyandito Restyandito (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
The situation and condition of the spread of Covid-19 in Indonesia have forced everyone to reduce the intensity of going out of the house, including activities related to the need for health services. Therefore, a solution is needed so that people can meet their health needs without leaving the house. Taking into account that the elderly as the community group that is most vulnerable to contracting the virus and has the highest mortality rate, it can be said that the elderly is the group of people who most need online health services. Along with the growing penetration of internet usage and the increasing number of smartphone ownership in Indonesia, m-health is the right choice to help people access health services online via smartphones. KlikDokter is an example of m-health or a mobile-based application that provides various online health services. However, it was found that there were complaints that the KlikDokter application was too complicated and difficult for the elderly to use. From this problem, a usability test was finally carried out on the KlikDokter application interface, to identify what interface elements in the KlikDokter application were difficult for elderly users. The research respondents were divided into two groups with 16 and 17 people respectively. The first group is the elderly group aged >60 years. And the second group is the pre-elderly group with ages between 45 to 59 years. A pre-elderly group is a comparison group (control group). This test is carried out by measuring several aspects of usability, namely effectiveness, efficiency, user satisfaction, error, and cognitive load.